Stabilization of the obesity epidemic and increasing thinness in children in Caribbean Bonaire - Joana Kist-van Holthe; Tirza Blom; Laura Melchers; Alcira Janga-Jansen; Tahirih van Kanten; Marian Luinstra-Passchier; Teatske Altenburg; Remy HiraSing; Mai Chinapaw (BMC, 2018)
Abstract Background In 2008, the prevalence of overweight and obesity among children in Bonaire was twice as high as the prevalence in northern Europe but comparable to that of other Caribbean islands and the United States. The aim of this study was to examine change in the body mass index status of children in Bonaire and report children's energy balance-related behaviours (EBRB) in 2015. Methods Two school-based cross sectional surveys of children age 4-14 years were conducted in 2008 and 2015. Height (m) and weight (kg) were measured, body mass index (BMI) calculated and children's BMI categorised according to the International Obesity Task Force criteria. In 2015, children age 10-14 years completed a questionnaire on EBRB and responses were compared between non-overweight/obese children and overweight/obese children. Results In total 2117 children age 4-14 years participated (92.4% response rate). The prevalence of thinness significantly increased between 2008 and 2015 (adjusted OR 1.5 95% CI: 1.2-1.8). There were no other significant differences in children's weight status between survey years. One quarter of children (25.4%) were overweight/obese in 2015. There were no significant differences in EBRB between non-overweight/obese and overweight/obese children in 2015. Few children met recommendations for EBRB. Conclusions The prevalence of overweight/obesity in children in Bonaire did not significantly change between 2008 and 2015 and remained high. However, the prevalence of thinness has significantly increased. Interventions to improve children's current EBRB are required.